Pengaruh Risiko dan Efisiensi Operasional terhadap Profitabilitas: Peran Moderasi Komposisi Dewan Direksi Perempuan pada Bank Pemerintah Daerah - Indrihartini, Tjong; Lutfi, Lufti (Faculty of Economic and Business Universitas STIKUBANK, 2025)
This study aims to examine the impact of credit risk, liquidity, and operational efficiency on the profitability of Regional Government Banks (BPD) in Indonesia, and to explore the moderating role of female commissioners on the relationship between credit risk and profitability. The research uses a quantitative approach with secondary data from 2020 to 2024, utilizing regression analysis. The findings indicate that liquidity (LDR) and operational efficiency (BOPO) have a significant positive impact on profitability (ROA), while credit risk (NPL) does not significantly affect profitability. The presence of female commissioners shows a negative effect in the direct model, but this becomes insignificant with moderation, suggesting that the influence of gender diversity in banking governance may differ depending on the context. The study contributes to the literature by highlighting the critical role of liquidity management and operational efficiency in enhancing profitability, and offers practical implications for improving governance and performance in Regional Government Bank.